The Mastery of The Fifth Semester Students of English Department of FKIP UKI Toraja In Translating English Idioms In A Sentence Context - Selvi Panggua (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2012)
The objectives of the research are to find out The Mastery of the Fifth Semester Students of English Department of FKIP UKI Toraja and also find out the factors influence the Mastery of fifth semester students of English Department of FKIP UKI Toraja in translating English idioms in a sentence context The design of the research is descriptive method. The Population of this research is The Fifth Semester Students of English Department of FKIP UKI Toraja which three classes the total number of them is seventy five (75), The writer was choose a part of them as sample by using cluster sampling technique, in that class number of the students is twenty three (23). The instruments used to gather the data obtained from the test are analyzed by using the mean score analysis and the data obtained from questionnaires are analyzed by frequency and percentage technique and some factors influence as mention above. The result of the analysis collected through written test showed that the mean score is 3.5 and falls into very bad category. And the finding from questionnaires are caused by several factors, as follow : The students difficult in doing Translation’s assigment, The students don’t have much time read books about idioms, The students don’t have more books about idioms, The students assume that the using idioms in learning english specially in conversation is sometimes. Based on the resulted above the writer concludes that the mastery of fifth semester student of English Department of FKIP UKI Toraja in Translating English idioms in a sentence context still low.